Ocrelizumab in relapsing and primary progressive multiple sclerosis: Pharmacokinetic and pharmacodynamic analyses of OPERA I, OPERA II and ORATORIO. Issue 6 (7th December 2020) - Gibiansky, Ekaterina; Petry, Claire; Mercier, Francois; Günther, Andreas; Herman, Ann; Kappos, Ludwig; Hauser, Stephen; Yamamoto, Yumi; Wang, Qing; Model, Fabian; Kletzl, Heidemarie
Abstract : Aims: Ocrelizumab is a humanized monoclonal antibody that selectively targets CD20‐positive B cells and is indicated for treatment of patients with relapsing forms of multiple sclerosis (RMS) or primary progressive multiple sclerosis (PPMS). The pharmacokinetics and pharmacodynamics of ocrelizumab in patients with RMS or PPMS were assessed. Methods: A population pharmacokinetic model was developed based on data from the Phase II study and the Phase III studies OPERA I and OPERA II in patients with RMS. Data from the ORATORIO Phase III study in patients with PPMS became available after model finalization and was used for external model evaluation. Results: The ocrelizumab serum concentration vs time course was accurately described by a 2‐compartment model with time‐dependent clearance. Body weight was found to be the main covariate. The area under the concentration–time curve over the dosing interval was estimated to be 26% higher for patients with RMS weighing <60 kg and 21% lower for patients weighing >90 kg when compared with the 60–90 kg group. The terminal half‐life of ocrelizumab was estimated as 26 days. The extent of B‐cell depletion in blood, as the pharmacodynamic marker, was greater with increasing ocrelizumab exposure. Conclusion: The pharmacokinetics of ocrelizumab was described with pharmacokinetic parameters typical for an immunoglobulin G1 monoclonal antibody, with body weight as the main covariate. The pharmacokinetics and B‐cell depletion in blood were comparable across the RMS and PPMS trials, and the extent of blood B‐cell depletion was greater with higher exposure.